Conversion of UKA to TKA using identical standard implants—How does it compare to primary UKA, primary TKA and revision TKA? - Christian B. Scheele; Matthias F. Pietschmann; Thomas C. Wagner; Peter E. Müller (Arthroplasty, 2024)
Abstract Background UKA is a well-established treatment option for anteromedial osteoarthritis of the knee, resulting in superior functional outcomes but also higher revision rates than TKA. This study aimed to compare the outcomes of UKA, TKA, UKA converted to TKA using identical standard implants and revised TKA to support clinical decision-making. Methods In this study, we retrospectively examined 116 patients who underwent UKA, 77 patients who received TKA, 28 patients whose UKA was converted to TKA using identical standard implants, and 21 patients who had a one-stage revision of TKA. The mean age at operation was 66.5 years (39–90 years), with a mean BMI of 28.8 kg/m2 (17.4–58.8) and a mean follow-up period of four years (0.9–9.9 years). We assessed various PROMs, including Oxford Knee Score, UCLA score, KSS score, and a modified WOMAC-Score as well as patient satisfaction and ability to resume daily activities, work, and sports. Results The highest patient satisfaction was seen in the UKA. All scores were significantly higher for UKA than for TKA, converted UKA, and revised TKA. None of the scores showed a significant inferiority of converted UKA to TKA. In the case of revision, two scores showed significantly better results for converted UKA than for revised TKA. Conclusions Our results indicated that patients initially treated with UKA did not have significantly worse functional outcomes after conversion to TKA, given the use of identical standard implants. This highlights the effectiveness of UKA as a therapeutic option with outcomes superior to those of primary TKA and the importance of a bone-sparing procedure. Conversely, revision TKA is linked to poorer functional outcomes compared to both primary arthroplasties.